Numerical Study on Flow Characteristics in a Francis Turbine during Load Rejection - Daqing Zhou (Energies, 2019)
Labyrinth seals are not usually included in the numerical models of hydraulic machinery to simplify the geometric modeling, and thereby reduce the calculation burden. However, this simplification affects the numerical results, especially in the load rejection process, because disc friction losses, volume losses, and pressure fluctuations in the seal ring (SR) clearance passage are neglected. This paper addresses the issue by considering all of the geometrical details of labyrinth seals when conducting multiscale flow simulations of a high head Francis turbine under a transient load rejection condition using the commercial software code. A comparison of the numerical results that were obtained with the experimental testing data indicates that the calculated values of both torque and mass discharge rate are 8.65% and 5% slightly less than the corresponding values that were obtained from experimental model testing, respectively. The obtained pressure fluctuations of the Francis turbine in the vaneless zone and the draft tube appear to more closely match with the experimental test data when including SR clearance. Moreover, the flow rates through SR clearance passages were very small, but the pressure fluctuations among them were significantly enhanced under the minimal load condition. The numerical model with SR clearance can more accurately reflect the fact that the water thrust on the runner only fluctuates from 800 N to 575 N during the load rejection process, even though the water thrust on the blades varies from −220 N to 1200 N. Therefore, multiscale flow study is of great significance in understanding the effect of clearance flow on the load rejection process in the Francis turbine.